Emily Brontë’s Wuthering Heights In Indonesian Version: Lulu Wijaya’s Translation Strategies and Inappropriateness Explored - Maria Lucia Luciana (Jurnal Pendidikan Humaniora, 2014)
Abstract: This study is aimed at providing the answers to the two research questions proposed. First, it is to examine the strategies used by Lulu Wijaya in translating Emily Brontë’s Wuthering Heights. Second, it is to explore how inappropriate Lulu Wijaya’s translation of Emily Brontë’s Wuthering Heights is. The research data were obtained from both the English and the Indonesian versions of the novel under discussion. The data were then analyzed dealing with the translation strategies and the researcher’s suggested translation version for the inappropriate translation. The suggested translation version was later validated by two validators to make sure that the research results would not be biased. The research shows that there are 10 translation strategies used in the translation, namely synonymy, literal translation, paraphrase, deletion, hyponymy, free translation, emphasis change, modulation, borrowing, and abstraction change. It also proves that the translator’s translation is inappropriate with both validators agree about 90% with the researcher’s suggested translation. Key Words: translation strategies, inappropriateness Abstrak: Penelitian ini bertujuan untuk menguji strategi yang digunakan oleh Lulu Wijaya dalam me-nerjemahkan Novel Emily Brontë Wuthering Heights dan untuk mengeksplorasi bagaimana ketidaksesuaian terjemahan Lulu Wijaya terhadap Novel Emily Brontë Wuthering Heights. Data penelitian diperoleh dari novel yang sedang dibahas dalam bahasa Inggris dan versi Indonesia. Data dianalisis terkait dengan strategi penerjemahan dan menyarankan terjemahan versi peneliti untuk terjemahan yang tidak sesuai. Terjemahan versi peneliti kemudian divalidasi oleh dua validator untuk memastikan bahwa hasil penelitian tidak akan bias. Hasil penelitian menunjukkan bahwa ada 10 strategi penerjemahan yang digunakan, yaitu sinonim, terjemahan harfiah, parafrase, penghapusan, hiponimi, terjemahan bebas, perubahan penekanan, modulasi, pinjaman, dan perubahan abstraksi. Hal ini membuktikan terjemahan Lulu Wijaya tidak tepat, kedua validator setuju sekitar 90% dengan terjemahan yang disarankan peneliti.Kata kunci: strategi penerjemahan, ketidaksesuaian